LOCAD AND GLOBAL STRENGTHENING OF WOOD BEAMS DURING OPERATION (Collection of scientific works «Modern structures of metal and wood», 2024)
The work presents modern comprehensive methods for the rehabilitation and reinforcement of glued wooden beams or timbers that can be utilized during their service in buildings. The  local  or  global  reinforcement  of  wooden  elements  made  of  solid  or  glued  wood,  which  are subjected to transverse bending, needs to be performed either with full or partial unloading of the structure. The reinforcement effect is greater with complete unloading of the structure compared to partial unloading.  Local  reinforcement  of  the  structure,  through  altering  the  physical  and  mechanical properties of the material in problematic areas, often involves the injection of cracks with adhesives followed by the application of the chosen reinforcement system. Global reinforcement of wooden bending elements includes reinforcing both the compressed and tension zones of the element, as reinforcing only the tension zone provides minimal effect. The best  effect in global reinforcement of beam structures is achieved through double reinforcement, either with  high-grade steel reinforcement bars or by reinforcing the tension zone with polymer tapes while simultaneously installing steel reinforcement in the compressed zone. Often, global reinforcement of both the compressed and tension zones of wooden beams results in insufficient shear bearing capacity. Therefore, a comprehensive approach toreinforcing wooden beams as a whole necessitates reinforcing the element’s ability to handle increased shear forces at the edges. An effective method for increasing the shear force capacity of a wooden beam is reinforcing it by bonding one or more composite strips at a 45-degree angle. The bonding is performed using polymer adhesives at specific intervals on both sides of the beam in areas close to the supports. The  issue  of  reinforcing  wooden  structures  in  service  is  quite  complex  and  requires  an individual approach in each case. The comprehensive development of methods for reinforcing wooden bending elements is currently hampered by the lack of regulatory framework in Ukraine to address this issue. At the time, there was no general work on reinforcement. Each engineer developed his own methods for reinforcing timber bending members.